Who's Afraid of James Joyce? - Lawrence, Karen R. (Florida James Joyce., 2010)
The development of Joycean studies into a respected and very large subdiscipline of modernist studies can be traced to the work of several important scholars. Among those who did the most to document Joyce's work, Karen Lawrence can easily be considered one of that elite cadre. A retrospective of decades of work on Joyce, this collection includes published journal articles, book chapters, and selections from her best known work (all updated and revised), along with one new essay. Featuring engaging close readings of such Joyce works as Dubliners and Ulysses, it will be a welcome addition to.